Determination of amylose content of traditional rice varieties of Kerala using PCR-based molecular markers - John, Deepa; Raman, Maya (ORYZA-An International Journal of Rice, 2023)
The present study uses molecular approach to assess the amount of amylose in collected rice genotypes using PCR based markers. The polymorphism of Waxy allele which encodes the major enzyme catalyzing amylose synthesis was analyzed in the collected rice samples to determine the amylose content in the samples. All the rice varieties under study expressed Wxa allele corresponding to intermediate to high amylose content. This study proves that simple PCR technique can be used to detect Single nucleotide polymorphism mutation at Wx locus and provides a cost-effective alternative to predict amylose content in rice.